Corporate governance and its impact on firm risk - Abdullah Alam; Syed Zulfiqar Ali Shah (International Journal of Management, Economics and Social Sciences (IJMESS), 2013)
The aim of this research is to explore the relationship of corporate governance with firm risk. This study establishes a link between corporate governance variables and firm risk for a sample of 106 Pakistani firms over a time of six years (2005-2010). Based on the estimation results, family control and bank control have negative impact on the firm risk whereas ownership structure and chairman/CEO duality posit positive relationship with risk. This provides a direction for firms to introduce more non-family control to the board of directors and not allow banks to have majority shareholding in their stocks. Also, directors should be asked to have a reasonable ownership in the stocks of the firm so that they can decide in the best interest of the firm and for the increase of their stock value. Chief executive should also hold the chair in order to have unity of command and a better decision-making influence.
Keywords: G21; G32; G34; 330; corporate finance; corporate governance; firm risk; system GMM